Vitamin D and Type 2 Diabetes Mellitus: Role in Insulin Resistance, Glycemic Control and Long Term Complications - Indah Sapta Wardani; Aliza Raudatin Sahly; Indana Eva Ajmala; Dewi Suryani (Faculty of Medicine Universitas Mataram, 2022)
Vitamin D has a number of roles in various body systems with receptors scattered in many organs,1,2 showing a link between vitamin D and several chronic diseases such as cancer, diabetes and autoimmune disease.3,4 Several studies have shown the role of vitamin D in type 2 diabetes in controlling blood sugar levels and HbA1c levels. Vitamin D plays a role in increasing insulin sensitivity and secretion and suppressing inflammation in type 2 diabetes. Vitamin D has a protective role in various complications of type 2 diabetes, including diabetic nephropathy, diabetic neuropathy and diabetic retinopathy.5 Monitoring of vitamin D levels and vitamin D supplementation have a therapeutic role to controlling glycemic blood glucose and prevent complications in type 2.6